Lectura y su incidencia en el desarrollo del pensamiento crítico de los estudiantes del séptimo año de la U. E. 24 de Mayo de Puebloviejo - Nieto Crespo, Clementina Martha (2023)
This investigative work was carried out in the Babahoyo canton, Province of Los Ríos in the 24 de Mayo educational unit, whose objective of the study was to determine how reading affects the development of critical thinking in seventh-year students of the U.E. May 24, Pueblo Viejo where the general problem is that students have poor reading skills, lack interest in reading, and lack critical thinking. For the development of this research, the bibliographic review and the quantitative method were used as methodology, since surveys were carried out on 30 students in the seventh year of basic education of this institution. An analysis of these surveys was also carried out in order to obtain the results obtained where, according to the way that the students read and the continuous use that they give to reading, their critical thinking will depend on different situations such as thinking correctly or choosing the right way to read. best alternative solution, that is, one must understand the ideas and information in the text and apply that knowledge to one's life, in addition, students must also understand that they need to practice their reading skills to improve in the general conclusions and While it is important for students to understand what they are reading and develop their thinking skills, poor readers often find it difficult to follow directions when presented with writing tasks.